Analysis and Optical System Design of the Lenslet-Array Integral Field Spectrometer - Jianan Liu; Jing Cui; Haodong Shi; Qi Wang; Zhuang Liu; Yingchao Li; Peipei Wang; Qiang Fu; Chao Wang (Photonics, 2023)
To address the problem of slit limitation in traditional slit imaging spectrometers, which hampers fast the identification, efficient tracking, and precise avoidance of faint targets in lunar orbit, this article proposes a lenslet-array integral field spectrometer structure that is free of slits, static, and that is fast and efficient for the visible-to-near-infrared wavelength band. Firstly, the field of view segmentation model is analyzed, and the requirement of the telecentric degree of the pre-imaging system is obtained. Secondly, the influence of aberrations, such as spherical aberration and coma distortion on the micro-pupil dispersion model is analyzed. Based on this, the pre-imaging system is designed to meet the requirements of aberration correction and the telecentricity of the system. Finally, the structure of the spectral system is designed, and the integrated system is optimized. The smile of the lenslet-array integral field spectrometer is ±1 nm, and the MTF is greater than 0.7 at 60 lp/mm and close to the diffraction limit.